In Vitro Anticoagulant Activity of Crude Protease of Bacillus tequilensis HSFI-5 - Stalis Norma Ethica; Tri Joko Raharjo; Dewi Seswita Zilda; Nur Hidayati (Universitas Nahdlatul Ulama Surabaya, 2023)
obtained from the fermented intestine of Holothuria scabra (sand sea cucumber). Strain HSFI-5 had been reported to be able to produce proteases, which had shown several characteristics of an antithrombotic agent, i.e., fibrinolytic and clot-lysis activities. However, its anticoagulation activity test is yest to be done. This study aimed to determine the anticoagulant activity of the crude protease HSFI-5 in vitro. The study design was a completely randomized design with a sample size of 90 calculated using the Federer formula. The material used was crude protease from B. tequilensis in skim milk broth. Prothrombin time (PT), activated partial thromboplastin time (aPTT), and plasma recalcification time (PRT) were carried out to test the anticoagulant activity. Citrated platelet poor plasma samples were divided into positive control, normal control, direct examination with crude enzyme in volumes of 50 and 100 µL and pre-incubation at 37ºC for 5, 10, and 15 min with crude enzyme volumes of 50 and 100 µL. The data normality was tested with the Kolmogorov-Smirnov test and the different tests were analyzed by one-way ANOVA with the Post hoc LSD test. The results of one-way ANOVA both on PT, aPTT, and PRT examinations showed that there was a significant difference between the treatment groups (p<0.05). The longest results of PT, aPTT, and PRT are positive controls, and the shortest results are normal controls for PT, and 15’ 50 group for aPTT and PRT. It is clear that crude protease B. tequilensis HSFI-5 exhibits anticoagulant as well as thrombolytic action, raising the possibility that it could function as an antithrombotic drug.